DISCUSSION ON INDIVIDUAL EDUCATIONAL TRAJECTORY AS AN INTEGRAL COMPONENT OF CONTINUOUS PROFESSIONAL DEVELOPMENT - Iryna Mazur; Nataliia Hasiuk; Myroslava Drohomyretska; Ivan Popovych; Volodymyr Radchuk (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2023)
The system of continuous professional development of doctors in Ukraine needs detailed analysis and comprehensive dynamic monitoring to become a process that includes the possibility of a doctor's professional growth. The research aims to monitor approaches to the continuous professional development of dentists for the formation and improvement of professional competence skills by highlighting the role of individual educational trajectory based on the priority of work formats with professional information, methods of familiarization with it and its receiving. 2216 respondents took part in the research, filling out a questionnaire during scientific and practical events of professional schools for dentists in online mode in March 2023, which included questions on the definition and objectification of forms, formats, ways of implementing continuous professional development and the vision of approaches to acquiring new knowledge and skills. The data obtained was processed using the StatSoft Inc licence program. Analytical research methods and structural-logical analysis were applied. According to the survey results, an individual's educational trajectory should include attending lectures, professional seminars, working with scientific and practical publications. The main quality requirement for publications is their good illustration of clinical cases and algorithms for working with patients. The analysis results of the rating parameters of professional dental journals declare the request of the dental community to improve the quality of material content, visual design and a possible change in positioning.